PENGARUH PENDIDIKAN DAN PELATIHAN KINERJA APARATUR PEMERINTAH DI KANTOR KECAMATAN KAWANGKOAN UTARA - WATUSEKE, AFNI M; POSUMAH, JOHNNY HANNY; Mambo, Rully (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: Government personnel is an important factor in achieving the objectives ofgovernment and state. In reality there is, still encountered problems in government agencies.Problems often occur is the presence of government officials who have the quality of work is notgood, it was seen from the slow processing tasks that accumulate, the lack of discipline ofgovernment officials, as a result of service that is provided is not maximized., While the one of thegovernment's efforts to improve the quality of government personnel is by giving knowledge andguidance through education and training.The research method that I use in this study is a quantitative research methods.quantitative method is a method / research based on the philosophy of positivism that is the sciencevalid, science is built on empirical, observable, measurable, using mathematical logic and makegeneralizations above average population and sample of this research is all employees at thedistrict office Kawangkoan north numbering 30 people.Based on the analysis using Pearson product moment correlation coefficient (r) = 0.802,while the coefficient of determination (r2) = 0.64. The results showed that the correlationcoefficient between the level of education and training on the performance of government officialsby 0802, while the coefficient of determination of 64%. With this result can be explained that theincrease in the performance of the government apparatus is determined by the education andtraining by 64% while 36% is determined by factors other. be based on above results, thehypothesis put forward unacceptable that there are degrees of connection and the power ofdetermination between education and training on the performance of government officials at theDistrict Office North Kawangkoan. Furthermore, based on the significance of test results obtainedthat the value t = 7108 at significance level (Î±) = 0.05 with degrees of freedom (df) = n -2 = 28,then the table = 1.701. From the data obtained that thitung greater than table where thitung 7.108Ëƒ 1,701. then H0 and H1 a reject. thing this proves that there is significant influence betweeneducation and training on the performance of government officials at the District Office NorthKawangkoan.of research results on North District office Kawangkoan that education andtraining programs have a very strong influence on the improvement of the performance of thegovernment apparatus, the more often a government apparatus to follow the education andtraining programs, the performance of the apparatus will also increase.Keywords: education and training, government officials Performance